TAREKAT NAQSYBANDIYA BABUSSALAM: Situs, Silsilah dan Jaringan - Ziaulhaq Ziaulhaq (Turast: Jurnal Penelitian dan Pengabdian, 2014)
This paper is in terms of the site, the pedigree and  the network of Tarekat Naqsabandiya Babusalam (TNB).The structure of this paper is divided based on focus assessment in the site, the pedigree and the network ofTNB. So far this study found that the site of TNB is located in Langkat, North Sumatra, which early also hada special relationship with local authority of Langkat, when Langkat was still be a kingdom, so the spread ofBNP in this area becomes more massive because it is supported by the power. Furthermore, TNB has a centralarea which called Babussalam, a village of Naqsybandiya. The pedigree of TNB is connected to SulaimanZuhdi, a murshid of Naqsybandiya who based in Jabal Abi Qubis and then through Zuhdi is connected withthe clergy of other tharekat until the Prophet Muhammad. The network of TNB in Indonesia include NorthSumatra, West Sumatra, Riau, Aceh and West Java, which also assume spreading to other areas. In overseas,TNB has a strong network in malay countries such as Malaysia Singapore to China, but to last state lost contact.